KOMUNIKASI POLITIK DEWAN PIMPINAN CABANG (DPC) PARTAI PERSATUAN INDONESIA (PERINDO) DALAM MEREKRUT PENGURUS DI KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI - Sikza Linda Sari; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
A crisis of public confidence in the political parties become an obstacle for the political parties to attract the public, especially for the new party. PERINDO party comes as a new party in the political world. As a new party must be good at recruiting party administrators so as to strengthen the party's internal structure and simplify the process of verifying the electoral process to come. Targeted recruitment of officials in Indonesian to 1.5 million people board. For this study aims to find out how political communication strategies branch executive council (DPC) PERINDO party in recruiting administrators in District Kuantan Mudik, regency kuantan Singingi and to find out how political persuasion branch executive council (DPC) PERINDO party in recruiting board.This research method is a qualitative method using the theory of Lasswell. The informant of this study consisted of 5 people branch executive council (DPC) PERINDO party the district Kuantan Mudik and 5 Management Branch (village). The technique of collecting data using interviews, observation and documentation. For the data analysis, refer to the interactive model Huberman and Miles. For checking the validity of the data using the extension of participation and triangulation techniques.The results of this study indicate that political communication strategies used by branch executive council (DPC) includes five elements namely political communicator of political communication, political messages, media, politics, goals or targets and the effect of a communication made by branch executive council (DPC) District of Kuantan Mudik PERINDO party. Political persuasion made in recruiting board that is through advertising, rhetoric and social activities. With the communication strategy undertaken by the branch executive council (DPC) PERINDO party, With the communication strategy undertaken by the branch executive council (DPC) PERINDO party, the branch executive council (DPC) Kuantan Mudik PERINDO party managed to recruit administrators twigs in accordance with the target that has been set.Keyword : Political Parties, Political Communication Strategies, Political Persuasion